Polarization switching and fatigue characteristics of highly (117)-oriented Bi3.15Nd0.85Ti2.99Mn0.01O12 ferroelectric thin films at both low and elevated temperatures. Issue 34 (12th April 2017) - Zhang, W. L.; Tang, M. H.; Xiong, Y.; Yan, S. A.; Cheng, C. P.; Li, G.; Xiao, Y. G.; Li, Z.
Abstract : Polarization switching and fatigue properties of BNTM ferroelectric thin films were studied from 100 to 475 K. A combination of impedance spectra and PFM techniques was used to analyze the mechanisms of the dependence on temperature from 200 to 475 K. Abstract : Polarization switching and fatigue properties of highly (117)-oriented Bi3.15 Nd0.85 Ti2.99 Mn0.01 O12 (BNTM) ferroelectric thin films were studied at both low and elevated temperatures (100 K up to 475 K). The fatigue behavior of BNTM thin films displays little dependence on temperature below 200 K, which can be explained by a weak domain wall pinning and unpinning effect. In the temperature range of 200 and 300 K, the polarization fatigue of BNTM films becomes exacerbated, which can be ascribed to a stronger domain pinning effect and increased electron injection from the Schottky barrier at film/electrode interfaces. However, the films showed improved fatigue endurance as the temperature increases from 300 to 400 K. From the temperature-dependent impedance spectra analysis we have learned that the long-range diffusion of oxygen vacancies within their clusters and strong domain unpinning effect may be responsible for this trend. Using the in-plane PFM phase image, observations of the microscopic evolution of domains and charged domain walls were made, and charged domain walls caused by head-to-head or tail-to-tail polarization configurations were found. Thus a combination of impedance spectra techniques and PFM domain observations can be a powerful technique, and has been used in this study to analyze the mechanisms of polarization fatigue at both low and elevated temperatures for the layered perovskite structure BNTM thin films.